(3cJGH aj GdWHs ((3bSWfWjfI s)
(3ChdgG (B:s
(3GdbhjI GdTOjOI hGdWHN GdWhjd hGdefbhY CNa ef GdeWHhN hCHQO CjVG s
(3BNQgG (B:s
(3hbY GdaQGZ ef JYdjbg ai eOjfI bSWfWjfI ai JGQjN SfI KdGK YTQ hJSYeGFI hbO cJH KdGKI CQHGYg YHO GdQMje Hf HGHGq s
(3GdfSNI HgG MhGTs
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdhWfjI HJhfS (B(3665) s
Keywords: (3GdWHs